Johann Adolph Scheibe (1708–76) and Copenhagen - Hauge, Peter (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
Peter Hauge: J.A. Scheibe and Copenhagen Johann Adolph Scheibe (1708−1776), a German composer and theorist, settled in Denmark in 1740 employed as Christian VI’s new chapel master. He is, in particular, known for his periodical Critischer Musikus published during the years 1737−40 in which he includes a famous critique of J.S. Bach’s musical style. Though Scheibe was indeed a highly productive and popular composer in his day his works are rather unknown and the majority of them are only available in manuscript in the collections of The Royal Library, among other places. The first part of the article deals with Scheibe’s connections with members of the the circle of intellectual immigrants that settled in Copenhagen during the eighteenth century, which included J.E. Schlegel, F.G. Klopstock, H.W. Gerstenberg, J.A. Cramer and J.B. Basedow. The subjects in which they showed a great interest were for instance the relationship between text and music, but also subjects such as education, history (Scandinavian), language, religion and philology were given due attention. The second part of the article discusses the problems involved in establishing a complete list of Scheibe’s works, in particular his compositions. For instance, should the list only include works that have survived or should it also include those which are referred to in contemporary sources such as newspapers, journals and published booklets but have since been lost? And how may such a list reflect Scheibe’s importance for the musical environment in Copenhagen during the second half of the eighteenth century?